Net Zero Energy Buildings - Samyukta Shrestha; Sweta Shrestha (KEC Journal of Science and Engineering, 2025)
Net Zero Energy Buildings (NZEBs) have emerged as a cornerstone in sustainable development, aiming to balance energy consumption with renewable energy production. This paper explores the principles, technological strategies, and practical implementations of NZEBs. By integrating insights from case studies and theoretical frameworks, the study provides a comprehensive understanding of the challenges and solutions in achieving energy efficiency in buildings. The findings aim to inform architects, engineers, and policymakers about advancing the built environment’s sustainability.